Time synchronization and interference mitigation scheme in heterogeneous network - Mohammad Kamrul Hasan (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
Recently, Orthogonal Frequency-Division Multiple-Access (OFDMA) based Heterogeneous Network (HetNet) achieves the desired capacity and coverage for indoors through the deployment of femtocells (HeNB). These HeNBs are plug-and-play Customer Premises Equipment's (CPEs) which are associated over the Internet Protocol (IP) backhaul to macrocell (macro-eNodeB). The random placement of HeNBs which is deployed in co-channel along with macro-eNodeB is causing severe degradation on system performance. These randomly placed HeNBs have been suggested as the cause of Co-Tier Interference (CTI) and Cross-Tier Interference (CSI) that can signiﬁcantly reduce the throughput, and the outages can rise to unacceptable limits. The HeNBs will experience synchronization issues when Internet backhaul connectivity is limited. These resulted inphase offset and phase skew. To alleviate these challenges, this study proposes Synchronization and Interference Mitigation scheme for HetNet (SIM-HetNet). It consists of Hybrid Self-organized Clustered Time Synchronization (HSCTS) scheme capable of rectifying the phase offsets as well as phase skews in terms of HeNBs' synchronization. The scheme also incorporates a Dynamic Subcarrier Allocation (DSA) scheme to mitigate interference (CTI and CSI) issues. The DSA scheme consists of Hybrid of Genetic and Biogeography based Dynamic Subcarrier Allocation for Co-Tier Interference (HGBBDSA-CTI) mitigation, and Evolutionary Biogeography based Dynamic Subcarrier Allocation for Cross-Tier Interference (EBBDSA-CSI) mitigation techniques. The evaluation of the proposed SIM-HetNet scheme were carried out using Monte Carlo simulation in MATLAB for HSCTS scheme and the DSA scheme were executed via system level simulation. Among the deliberated performance metrics are phase offset, phase skew, min-max throughput, outage rate, spectral efficiency, and Signal to Interference Noise Ratio (SINR). The findings suggested that phase offset can be reduced by 65.5% when compared to the standard IEEE 1588 for Packet Transmission Network (IEEE 1588 PTN), the average phase offsetis minimized to 99.94% in compare with Enhanced IEEE 1588 E (IEEE 1588 E) standard, and the phase skew can be minimized down to 91% when compared to the Mobile Assisted Time Synchronization (MATS) scheme. The research outcomes show that the proposed HGBBDSA-CTI technique outperforms the benchmarked Genetic Algorithm (GA) based DSA and Particle Swarm Optimization (PSO) based DSA in terms of increased average throughput (92.05%, and 74.44%), increased throughput (30.50% and 74.34%), and reduced the outage rate (52.9%, and 50.76%). Whereas, the EBBDSA-CSI technique's total spectral efficiency achieves improvement of 83.6%, and managed to reduce outage probability down to 88.1% when compared to Fractional Frequency Reuse (FFR) based DSA.